THE EFFECT OF SUSTAINABILITY REPORT DISCLOSURE AND COMPANY SIZE ON MARKET REACTION MODERATED BY SUSTAINABILITY REPORT ASSURANCE IN COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE IN 2019 - 2023 - Fadilla, Nadya; Yenti, Riza Reni (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
This study is inspired by the need to share sustainability data to boost investor trust, particularly in the face of challenges related to upholding a favorable corporate reputation. The main goal of this study is to investigate the effect of revealing sustainability reports and the company's size on market reaction, considering the role of sustainability report assurance as a moderating element. The research relies on data from sustainability and financial reports of companies on the Indonesia Stock Exchange between 2019 and 2023. Researcher employed multiple linear regression and Moderated Regression Analysis (MRA) as the analysis techniques. The findings showed that sustainability report disclosure has a significant effect on market reaction, while company size does not show a significant effect. In addition, sustainability report assurance is unable to moderate the relationship between sustainability report disclosure and market reaction. This study underscores the importance of comprehensive sustainability report disclosure to attract positive market reactions, although the role of assurance still needs to be improved. The implication of this research is the need for companies to strengthen sustainability reporting in accordance with international guidelines and consider additional strategies to increase credibility and investor appeal.